The Effect of Wordscapes Application Toward Students Vocabulary Mastery at the Seventh Grade of Al-Um Islamic Boarding School Nort Bengkulu - Nur Hidayah; Ferri Susanto; Dedi Efrizal (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aimed to determine the effect of using the Wordscapes application on the vocabulary mastery of seventh-grade students at MTs Al-Um Islamic Boarding School, North Bengkulu Regency, in the 2024/2025 academic year. The research employed a quasi-experimental method with a nonequivalent control group design. The sample consisted of two classes: experimental and control. The research instrument was a vocabulary test in the form of multiple-choice questions, administered before and after the treatment. Data analysis was carried out using SPSS version 28. A validity test was conducted on 65 items, resulting in 26 valid questions. Furthermore, normality, homogeneity, t-test, and F-test were performed to determine the significance of score differences between the experimental and control groups. The results showed a significant increase in scores in the experimental class compared to the control class after being treated with the Wordscapes application. This indicates that the Wordscapes application is effective in enhancing students vocabulary mastery.